Exploring the Preventive and Restorative Functions of Lactobacillus pentosus in Flesh Deterioration Caused by Oxidized Fish Oil Diets in Hybrid Grouper (♀ Epinephelus fuscoguttatus×♂ E. lanceolatu). (9th August 2022) - Yan, Xiaobo; Li, Tao; Liu, Hao; Li, Zhihao; Tan, Beiping; Pan, Simiao; Huang, Weibin; Suo, Xiangxiang; Yang, Yuanzhi; Dong, Xiaohui
Abstract : The purpose was to investigate the preventive and restorative functions of Lactobacillus pentosus of hybrid grouper (♀ Epinephelus fuscoguttatus ×♂ E. lanceolatu ) flesh due to ingestion oxidized fish oil (OFO) diet. Basal diets were formulated using OFO as main lipid source and 1.0 × 10 9 CFU/g of L. pentosus was added to basal diet as experimental diet. Control group (OFO: 60 d basal diet), prevention group (OFOP: 30 d experimental diet + 30 d basal diet ), and restoration group (OFOR: 30 d basal diet + 30 d experimental diet ) were set up for grouper experiment with triplication. The results show that compared with the OFO group, the OFOP and OFOR groups significantly decreased muscle lipid deposition and lipid peroxidation production. The OFOP and OFOR groups significantly increased the polyunsaturated fatty acid content furthermore to improve nutritional value of muscle compared to the OFO group. Intervention with L. pentosus significantly influenced muscle flavor. OFOP and OFOR groups significantly upregulated expression of partial growth factor-related genes while downregulating expression of antioxidant-related genes. Consequently, the intervention of L. pentosus decreased lipid deposition and improved the nutritional value and flavor of grouper muscle, and it was recommended as a probiotic to prevent the deterioration of aquatic product quality.